2018
DOI: 10.1161/strokeaha.118.021961
|View full text |Cite
|
Sign up to set email alerts
|

Alberta Stroke Program Early CT Score Versus Computed Tomographic Perfusion to Predict Functional Outcome After Successful Reperfusion in Acute Ischemic Stroke

Abstract: Background and purpose We aimed to compare the ability of conventional Alberta Stroke Program Early Computed Tomography Score (ASPECTS), automated ASPECTS and ischemic core volume on CT perfusion (CTP) to predict clinical outcome in ischemic stroke due to large vessel occlusion up to 18 hours after symptom onset. Methods: We selected acute ischemic stroke patients from the Computed Tomography Perfusion to Predict Response to Recanalization in ischemic Stroke Project (CRISP) study with successful reperfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 20 publications
14
38
0
2
Order By: Relevance
“…Although ASPECTS values were not predictive of functional outcome in our study, they were predictive of final infarction volume concordant with prior reports. 34 Using automated ASPECTS, a recent study by Demeestere et al 34 showed findings similar to ours by demonstrating a lack of association with functional outcome but significant correlation in the determination of final infarction volume. We found 3 variables, including age, NIHSS, and final infarction volume, as significant contributors to predicting functional outcome.…”
Section: Discussionsupporting
confidence: 80%
“…Although ASPECTS values were not predictive of functional outcome in our study, they were predictive of final infarction volume concordant with prior reports. 34 Using automated ASPECTS, a recent study by Demeestere et al 34 showed findings similar to ours by demonstrating a lack of association with functional outcome but significant correlation in the determination of final infarction volume. We found 3 variables, including age, NIHSS, and final infarction volume, as significant contributors to predicting functional outcome.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, compared with preoperative multimodel imaging(CT or Magnetic resonance),LSAs has advantages of shorter time and easier operation, and provides potentially new decision-making factors for emergency thrombectomy in hospitals without preoperative evaluation of core infarction and ischemic penumbra. This study also confirmed the core infarct volume is an independent prognostic predictors for thrombectomy,which is similar to other studies [22][23][24] .…”
Section: Discussionsupporting
confidence: 92%
“…The assessment of LSAs on pre-interventional DSA provides potentially new decision-making factors for emergency thrombectomy in hospitals without preoperative evaluation of core infarct and ischemic penumbra. This study also confirmed the core infarct volume was an independently prognostic predictors for thrombectomy, which is similar to other studies [28][29][30].…”
Section: Discussionsupporting
confidence: 92%